The Effect of Using Social Media Marketing and Market Orientation on the Performance of Culinary MSMEs in Makassar - Mukhtar Galib; Siti Haerani; Jumidah Maming; Abdul Razak Munir (Proceeding of The International Conference on Economics and Business, 2022)
The goal of this study was to ascertain the impact of market orientation and social media marketing on the efficiency of the culinary MSMEs in Makassar. 40 respondents make up the entire sample in this causal study design. The non-probability sampling approach is used in the sampling procedure. Using the Smart PLS 3.0 application, data is processed. The findings of this study suggest that the performance of culinary MSMEs in Makassar is significantly influenced by the usage of social media marketing and market orientation.